Genetic basis for relapse rate in multiple sclerosis: Association with LRP2 genetic variation. (November 2018) - Hilven, Kelly; Vandebergh, Marijne; Smets, Ide; Mallants, Klara; Goris, An; Dubois, Bénédicte
Background: In contrast to successes for multiple sclerosis (MS) susceptibility, the genetic basis for clinical heterogeneity remains largely unresolved. Objectives: We investigate the first reported genetic association with relapse rate. Methods: We genotyped variant rs12988804 in LRP2 in a homogeneous study population of 527 Belgian MS patients with 970 documented relapses. Results: The rs12988804*T allele is associated with a 1.16-fold increased hazard rate for a relapse occurring ( P = 0.0078) and a higher baseline relapse rate prior to immunomodulatory treatment ( P = 0.044). Conclusion: Variant rs12988804 in LRP2, the first example of a genome-wide significant association with relapse rate in MS, is replicated in an independent study.